The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/tpj.14545
|View full text |Cite
|
Sign up to set email alerts
|

GmMAX2–D14 and –KAI interaction‐mediated SL and KAR signaling play essential roles in soybean root nodulation

Abstract: Summary Despite of important functions of strigolactones (SLs) and karrikins (KARs) in plant development, plant–parasite and plant–fungi interactions, their roles in soybean–rhizobia interaction remain elusive. SL/KAR signaling genes GmMAX2a, GmD14s, and GmKAIs are activated by rhizobia infection. GmMAX2a restored atmax2 root hair defects and soybean root hairs were changed in GmMAX2a overexpression (GmMAX2a‐OE) or knockdown (GmMAX2a‐KD) mutants. GmMAX2a‐KD gave fewer, whereas GmMAX2a‐OE produced more nodules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 69 publications
1
54
0
Order By: Relevance
“…The gene expression of BAHD members was analysed in RNA-Seq data derived from soybean nodules at different developing stages [1]. The results showed that BAHD genes were differentially expressed in the nodule at different developmental stages, from nodule development until its senescence ( Fig.…”
Section: Expression Profiles Of Bahd Genes During Nodule Development mentioning
confidence: 99%
See 1 more Smart Citation
“…The gene expression of BAHD members was analysed in RNA-Seq data derived from soybean nodules at different developing stages [1]. The results showed that BAHD genes were differentially expressed in the nodule at different developmental stages, from nodule development until its senescence ( Fig.…”
Section: Expression Profiles Of Bahd Genes During Nodule Development mentioning
confidence: 99%
“…Samples at different nodulation stages (N-1 to N-6) were obtained [1]. The seedlings were hydroponically subjected to acidic treatment (pH 4.0) and 50 mM Al 3+ stress (under pH 4.0) [2,82] for 10 days before harvesting the roots for gene expression analysis.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…From our analysis of RNA-Seq data derived from soybean nodules at different developing stages [78], BAHD genes were differentially expressed at different developmental stages of the nodule, since its development until senescence ( Fig. 7; Additional file 1: File S1b).…”
Section: Expression Profiles Of Bahd Genes During Nodule Development mentioning
confidence: 99%
“…These nodules at different developmental stages can be marked by average dry weights, from N1 to N6 were about 0.0005, 0.001, 0.004, 0.01, 0.03, 0.07 gram. [85,78]. The seedlings were hydroponically subjected to acidic treatment (pH 4.0) and 50 mM Al 3+ stress (under pH 4.0) [15,89] for 10 days before harvesting the roots for expression analysis.…”
Section: Plant Growth Rna-seq Data Analysis and Gene Expression Conmentioning
confidence: 99%
“…Similarly, the colonization of pea by arbuscular mycorrhizal resulted in a decrease in the germination rate of parasitic seeds due to a decrease in the content of SLs [130]. Moreover, arbuscular mycorrhizal colonization may inhibit the formation of legume nodules, due to the decrease in SL content [131]. For example, the root exudates of the SL-deficient rms1 mutant in pea have lower SL content and reduced nodulation capacity compared with the wild type, suggesting that SLs, as positive regulators of nodulation in peas, are necessary for optimal nodulation [118].…”
Section: Mycorrhizal Symbiosismentioning
confidence: 99%